Forgiveness, Flourishing, and Resilience: The Influences of Expressions of Spirituality on Mental Health Recovery. (1st April 2014) - Tuck, Inez; Anderson, Lorraine
<x xml:space="preserve">Abstract</x> The relationships of spirituality, religion, and health have been the subject of research in a variety of disciplines over the past two decades. Findings have varied: Some findings appear to have strong evidence of relationships while other findings are deemed inconclusive. A few studies have distinguished between religion and spirituality, but most investigators have treated the two as one concept with no clear lines of distinction between them. This theoretical study, focusing on the topic of spirituality, explores several related concepts, including forgiveness, flourishing, and resilience, as a basis for developing approaches to facilitate recovery in mental health clients using spiritual interventions.